A collaborative, academic approach to optimizing the national clinical research infrastructure: The first year of the Trial Innovation Network. Issue 4 (27th November 2018) - Bernard, Gordon R.; Harris, Paul A.; Pulley, Jill M.; Benjamin, Daniel K.; Dean, Jonathan Michael; Ford, Daniel E.; Hanley, Daniel F.; Selker, Harry P.; Wilkins, Consuelo H.
Abstract : Inefficiencies in the national clinical research infrastructure have been apparent for decades. The National Center for Advancing Translational Science—sponsored Clinical and Translational Science Award (CTSA) program is able to address such inefficiencies. The Trial Innovation Network (TIN) is a collaborative initiative with the CTSA program and other National Institutes of Health (NIH) Institutes and Centers that addresses critical roadblocks to accelerate the translation of novel interventions to clinical practice. The TIN's mission is to execute high-quality trials in a quick, cost-efficient manner. The TIN awardees are composed of 3 Trial Innovation Centers, the Recruitment Innovation Center, and the individual CTSA institutions that have identified TIN Liaison units. The TIN has launched a national scale single (central) Institutional Review Board system, master contracting agreements, quality-by-design approaches, novel recruitment support methods, and applies evidence-based strategies to recruitment and patient engagement. The TIN has received 113 submissions from 39 different CTSA institutions and 8 non-CTSA Institutions, with projects associated with 12 different NIH Institutes and Centers across a wide range of clinical/disease areas. Already more than 150 unique health systems/organizations are involved as sites in TIN-related multisite studies. The TIN will begin to capture data and metrics that quantify increased efficiency and quality improvement during operations.